Co-surgeon versus Single-surgeon Outcomes in Free Tissue Breast Reconstruction: A Meta-analysis - Xu, Joshua; Zhu, Xi Ming; Ng, Kimberly C.; Alhefzi, Muayyad M.; Avram, Ronen; Coroneos, Christopher J. (Journal of Reconstructive Microsurgery, 2024)
Background Autologous breast reconstruction offers superior long-term patient reported outcomes compared with implant-based reconstruction. Universal adoption of free tissue transfer has been hindered by procedural complexity and long operative time with microsurgery. In many specialties, co-surgeon (CS) approaches are reported to decrease operative time while improving surgical outcomes. This systematic review and meta-analysis synthesizes the available literature to evaluate the potential benefit of a CS approach in autologous free tissue breast reconstruction versus single-surgeon (SS).Methods A systematic review and meta-analysis was conducted using PubMed, Embase, and MEDLINE from inception to December 2022. Published reports comparing CS to SS approaches in uni- and bilateral autologous breast reconstruction were identified. Primary outcomes included operative time, postoperative outcomes, processes of care, and financial impact. Risk of bias was assessed and outcomes were characterized with effect sizes.Results Eight retrospective studies reporting on 9,425 patients were included. Compared with SS, CS approach was associated with a significantly shorter operative time (SMD −0.65, 95% confidence interval [CI] −1.01 to −0.29, p < 0.001), with the largest effect size in bilateral reconstructions (standardized mean difference [SMD] −1.02, 95% CI −1.37 to −0.67, p < 0.00001). CS was also associated with a significant decrease in length of hospitalization (SMD −0.39, 95% CI −0.71 to −0.07, p = 0.02). Odds of flap failure or surgical complications including surgical site infection, hematoma, fat necrosis, and reexploration were not significantly different.Conclusion CS free tissue breast reconstruction significantly shortens operative time and length of hospitalization compared with SS approaches without compromising postoperative outcomes. Further research should model processes and financial viability of its adoption in a variety of health care models.
Keywords: co-surgeon; autologous breast reconstruction; microsurgery; surgical outcomes